2015
DOI: 10.1515/amm-2015-0334
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Prediction Of Deformations In Laser Welded Sheets Made Of X5CrNi18-10 Steel

Abstract: The work concerns the numerical modelling of coupled thermal and mechanical phenomena occurring in the laser beam welding process. Commercial Abaqus FEA engineering software is adopted to numerical computations in order to perform a comprehensive analysis of thermo-mechanical phenomena. Created in Fortran programming language additional numerical subroutines are implemented into Abaqus solver, used to describe the power intensity distribution of the movable laser beam heat source. Temperature dependent thermom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 17 publications
(18 reference statements)
0
28
0
Order By: Relevance
“…The mechanical phenomena analysis in the elastic range was made using the equilibrium equations (1), which are supplemented by constitutive and Cauchy's equations (2), and boundary conditions (3). The mathematical model is based on solving the following system of equations [5,[8][9][10][11]:…”
Section: Mathematical Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanical phenomena analysis in the elastic range was made using the equilibrium equations (1), which are supplemented by constitutive and Cauchy's equations (2), and boundary conditions (3). The mathematical model is based on solving the following system of equations [5,[8][9][10][11]:…”
Section: Mathematical Descriptionmentioning
confidence: 99%
“…Displacement boundary conditions are used in the discussed problems [2][3][4][5][6][8][9][10][11]. The nodes located on the contact surface of the gantry crane beam with the support column on the right side of the beam can not displace in three directions (u x =u y =u z =0) and the left side in two directions (u x =u y =0) (Fig.…”
Section: Mathematical Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of the above-named steels entails research works concerning various technologies enabling the joining of such steels [20][21][22]. Increasingly often, metals and their alloys are joined using highly efficient welding processes enabling the obtainment of high-quality welded joints accompanied by high joining process efficiency and less labour.…”
Section: Introductionmentioning
confidence: 99%
“…Archard in 1957 was the first who found that the area of contact is approximately proportional to the normal force [5]. Nowadays advanced numerical methods such as finite element method (FEM) and the development of computer technology makes possible numerical modeling of complex problems [6][7][8]. This work aims to present a method of detecting collisions between objects surfaces and matching them during elastic deformation.…”
Section: Introductionmentioning
confidence: 99%